Antibacterial potential of symbiont bacteria of brown algae (Turbinaria conoides) obtained from Indonesian waters - Niken - Dharmayanti; ARMA ANTI; RESMI RUMENTA SIREGAR; YULIATI H. SIPAHUTAR; AEF PERMADI; ARPAN NASRI SIREGAR; RANDI BOKHI SALAMPESSY; SUJULIYANI SUJULIYANI; SITI ZACHRO NURBANI; Heni Budi Purnamasari (Society for Indonesian Biodiversity, 2021)
Abstract. Dharmayanti N, Anti A, Siregar RR, Sipahutar Y, Permadi A, Siregar AN, Salampessy RB, Sujuliyanti, Nurbani SZ, Purnamasari HB. 2021. Title. Biodiversitas 22: 373-378. Brown seaweeds have the potential to produce bioactive compounds. Bacteria associated with seaweeds are involved in the production of metabolites. Microbes may be present as a living symbiotic in association with other algae as epiphytes or endophytes. In this study, bacteria isolated from brown seaweed (Turbinaria conoides) were tested for antibacterial activity. A total of 14 bacteria were isolated, of which 6 were isolated from external tissue, while 8 from internal tissue. Results of an antagonistic test revealed that 7 isolates showed inhibitory activity against Staphylococcus aureus and only 1 isolate showed the inhibition against both S. aureus and Escherichia coli. Phenotypic and genotypic analysis showed that the symbiont bacteria was Lactobacillus plantarum.